Investigation of past earthquakes in the Kopili Fault zone, NE India: New evidence of paleoliquefaction - Lakshmi, B. V.; Baba, Mujahed; Gawali, Pravin B. (My University, 2022)
The Kopili Fault (KF) zone, one of the active faults in Northeastern region (NER), has experienced large earthquakes in 1869 (Mw 7.5) and 1943 (Mw 7.2). In order to mitigate future occurrences of earthquakes in the KF zone it is essential to understand its long term seismic history and seismic hazard implications. Seismogenic liquefaction features were identified at three trench sites in the floodplain deposits of Kolong River, near KF zone. The liquefaction features include multiple sand dykes, sand blows and flame like intrusion. These structures are direct response to a fluid escape during liquefaction mechanism and past seismic activity. The earthquake induced liquefaction features were dated at AD 1848-1915, AD 1782-1826, AD 1640-1770, AD 1540-1626, and AD 1057-1211. The liquefaction event dated at AD 1640-1770 may correlate with the 250±50 yr BP earthquake, recognized in an earlier study in the KF Zone, Assam. The late medieval liquefaction episodes were also identified in the study sites. The study sections also revealed sand dykes and sand blows that can be ascribed to the 1869 earthquake. The data generated in the present study deciphers five temporally close intervals of earthquakes of large types in the KF Zone during the last ~1000 years with a return period of ~200 years. Additional excavations and dating of earthquake induced liquefaction features is required to precisely evaluate the frequency of major earthquakes in the KF zone.
Keywords: Active fault; Earthquake; Kopili fault; Liquefaction features; Sand dyke; Sand blow